2021
DOI: 10.4037/ajcc2021245
|View full text |Cite
|
Sign up to set email alerts
|

Professional Identity During the COVID-19 Pandemic: A Cross-Sectional Survey of Nurses in China

Abstract: Background Emergency and intensive care unit nurses are the main workforce fighting against COVID-19. Their professional identity may affect whether they can actively participate and be competent in care tasks during the pandemic. Objective To examine the level of and changes in professional identity of Chinese emergency and intensive care unit nurses as the COVID-19 pandemic builds. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 41 publications
3
20
0
Order By: Relevance
“…This result is consistent with another study done by Zang et al [33]. Their results indicated that the most prevalent problem in the survey was altered self-image with (87.8%) of the screened frontline subjects; these results provide new insight into the relationship between dealing with a crisis like the COVID-19 pandemic and its impact on the frontline healthcare workers especially nurses.…”
Section: Professional Self-conceptsupporting
confidence: 91%
“…This result is consistent with another study done by Zang et al [33]. Their results indicated that the most prevalent problem in the survey was altered self-image with (87.8%) of the screened frontline subjects; these results provide new insight into the relationship between dealing with a crisis like the COVID-19 pandemic and its impact on the frontline healthcare workers especially nurses.…”
Section: Professional Self-conceptsupporting
confidence: 91%
“…This result is consistent with another study conducted by Zang et al [33]. Their results indicated that the most prevalent problem in their survey was altered self-image with (87.8%) of the screened frontline subjects; these results provide new insight into the relationship between dealing with a crisis such as the COVID-19 pandemic and its impact on frontline healthcare workers, especially nurses.…”
Section: Professional Self-conceptsupporting
confidence: 90%
“…This inconsistency may be related to the increasing concern on humanization in intensive care (Nin Vaeza et al, 2020). Especially after the outbreak of COVID‐19, nurses have received more attention and recognition from the public, which has inspired their sense of mission as ‘angel in white’, as well as stimulated their professional identity (Li et al, 2021; Zhang et al, 2021). As a result, nurses may focus more than ever before on caring and thus do a better job of maintaining patient dignity.…”
Section: Discussionmentioning
confidence: 99%